Edukasi Terapi Komplementer Kompres Bawang Merah Penurun Demam pada Balita Pasca Imunisasi DPT Melalui E-Leaflet - Heryani, Heni; Lestari, Lusi (Universitas Nusantara PGRI Kediri, 2023)
DPT immunization in children under five has one side effect, one of which is fever. One of the treatments for reducing fever in children after DPT immunization is by using complementary therapy, namely the use of onion compresses. Information on complementary therapies has not been maximally provided to the community, especially to parents of children under five after DPT immunization. In the midst of this covid pandemic, this information must still be provided, one of which is by providing information through the use of e-leaflets about the use of shallots for reducing fever in children after DPT immunization. Posyandu cadres are community members chosen from and by the community, willing and able to work together in various community activities voluntarily to deal with individual health problems and regular posyandu services. Through this posyandu cadre, it can be used as a means for disseminating information through e-Leaflets. It is hoped that this community service will increase the knowledge of posyandu cadres, so that they can provide information to mothers who have toddlers to use red bottom compresses as an alternative to reduce fever in toddlers after DPT immunization.